Exploring Classroom Discourse in Applied Linguistics: Analysing IRF Interaction Patterns in Offline and Online - Wati, Siska Oktawidya; Suzuasmisyah, Azza; Chair, Hafizul; Efrini, Multi (Journal of English Language and Education, 2025)
This study explores the dynamics of classroom discourse in offline and online English language classrooms, focusing on the Initiation-Response-Feedback (IRF) interaction pattern. While classroom discourse is critical for shaping language learning, research comparing interaction patterns in offline and online environments remains limited. This study aims to fill this gap by examining the IRF patterns in offline and online classes at UIN Mahmud Yunus Batusangkar, Indonesia. A qualitative approach was employed, involving classroom observations and analysis of recorded interactions between lecturers and students. The findings indicate that offline classrooms foster more balanced interactions, with the I R I R I R pattern being common. In contrast, online classrooms were dominated by lecturer-initiated exchanges, with the I I I R I pattern prevailing, reflecting the passive participation of students. Key findings highlight that student elicitation was absent in online learning, while it was present in offline settings. The study emphasizes the importance of adjusting teaching strategies in online environments to enhance student engagement and participation. Future research should explore how technological tools and different teaching methodologies affect interaction dynamics across various educational contexts